A Multisector Perspective on Wage Stagnation - L. Rachel Ngai; Orhun Sevinc (Institute of Labor Economics (IZA), 2023)
Low-skilled workers are concentrated in sectors that experience fast productivity growth and yet their real wages have been stagnating. We document evidence from the U.S. to show the importance of sectoral reallocations. Key to our two-sector model is the fall in the relative price of the low-skill intensive sector caused by faster productivity growth. When outputs are complements across sectors, this leads to a reallocation of low-skilled workers to the high-skill intensive sector where their marginal product is stagnant. We show that this mechanism is quantitatively important for the stagnation of low-skill real wages and their divergence from aggregate labor productivity during 1980-2010.
Keywords: E24; J23; J31; 330; wage stagnation; wage-productivity divergence; low-skill wage; multisector model